2003
DOI: 10.1007/s11745-006-1157-y
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of dietary palm oil concentration and water temperature on lipid digestibility in rainbow trout, Oncorhynchus mykiss

Abstract: An experiment was conducted to evaluate the interactive effects of dietary crude palm oil (CPO) concentration and water temperature on lipid and FA digestibility in rainbow trout. Four isolipidic diets with 0, 5, 10, or 20% (w/w) CPO, at the expense of fish oil, were formulated and fed to groups of trout maintained at water temperatures of 7, 10, or 15 degrees C. The apparent digestibility (AD) of the FA, measured using yttrium oxide as an inert marker, decreased with increasing chain length and increased with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
32
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 26 publications
9
32
0
Order By: Relevance
“…Obviously, the fatty acid composition of a vegetable oil alternative diet differs dramatically from the fatty acid composition of the FO and hence, dietary inclusion of RO and CSO at the expense of FO will affect the flesh fatty acid composition of the fish. LA, LNA and oleic acid were preferentially utilized in flesh, when present at high concentrations in the diet, as reported previously Ng et al, 2003). These data suggest that the monoene, oleic acid as well as LA and LNA, are readily oxidized when present in high concentrations.…”
Section: Discussionsupporting
confidence: 88%
“…Obviously, the fatty acid composition of a vegetable oil alternative diet differs dramatically from the fatty acid composition of the FO and hence, dietary inclusion of RO and CSO at the expense of FO will affect the flesh fatty acid composition of the fish. LA, LNA and oleic acid were preferentially utilized in flesh, when present at high concentrations in the diet, as reported previously Ng et al, 2003). These data suggest that the monoene, oleic acid as well as LA and LNA, are readily oxidized when present in high concentrations.…”
Section: Discussionsupporting
confidence: 88%
“…The positive relationship between tissue fatty acid composition and dietary fatty acid contents has been well demonstrated in previous studies (Bransden et al, 2005;Zia-Ul-haq et al, 2007a, b, 2008, 2011aLuo et al, 2008;Rezek et al, 2010). In this study, the muscle fatty acid composition in fish generally reflected the lipid composition in diets similar to the report of Ng et al (2003) that the high fatty acids in feed can lead to high fatty acids in muscle. Moreover, there were differences in fatty acid composition between fish muscle and the diets in our study.…”
Section: Discussionsupporting
confidence: 86%
“…The results of this study showed that the inclusion of CPO up to about 10 wt-% (25% of added oil) in Atlantic salmon feeds resulted in negligible differences in nutrient and fatty acid digestibility that did not affect growth performance of fish at the range of water temperatures generally encountered in the grow-out phase. In another study conducted with rainbow trout [24], we found that increasing dietary CPO levels and decreasing water temperatures significantly increased the triglyceride contents in trout fecal lipids, with saturates constituting more than 60% of the fatty acid composition. The reduction in apparent digestibility of saturated fatty acids was therefore due in part to the increasing resistance of dietary triglycerides rich in saturated fatty acids to digestion.…”
Section: Nutrient Digestibilitymentioning
confidence: 73%